2010
DOI: 10.1097/prs.0b013e3181da86d0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Nerve and Neuropeptide Patterns in Vacuum-Assisted Closure–Treated Diabetic Murine Wounds

Abstract: This study suggests that vacuum-assisted closure therapy can modulate nerve fiber and neuropeptide production in the wound. Optimized kinetics of vacuum-assisted closure application may provide an opportunity for clinicians to further improve wound healing in denervated wounds such as pressure sores and diabetic foot ulcerations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 35 publications
0
28
0
2
Order By: Relevance
“…7 Wound closure analysis shows no significant difference between wild-type and WWv mice; this is explained by splinting of our wounds and the epithelialization contact inhibition effect of the foam material as published previously. 23 Mast cell activation early in the healing process is suggested to affect later collagen production and maturation. 6,12 Our findings proved that microdeformational wound therapy exhibited a significant increase in collagen production and a faster maturation of the wound matrix into a permanent durable collagen matrix.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…7 Wound closure analysis shows no significant difference between wild-type and WWv mice; this is explained by splinting of our wounds and the epithelialization contact inhibition effect of the foam material as published previously. 23 Mast cell activation early in the healing process is suggested to affect later collagen production and maturation. 6,12 Our findings proved that microdeformational wound therapy exhibited a significant increase in collagen production and a faster maturation of the wound matrix into a permanent durable collagen matrix.…”
Section: Discussionmentioning
confidence: 98%
“…A suction tube is then inserted and secured over the dressing and linked to the pump. 19,23 Dressing changes were performed on days 2, 4, 7, 10, and 14 after excision with digital photography for wound planimetry. On days 1, 2, 7, and 14, animals were killed, with tissue fixed in 10% neutral-buffered formalin solution and kept in 70% alcohol at 4°C until paraffin or JB-4 glycol methacrylate embedment.…”
Section: Animals and Wound Modelmentioning
confidence: 99%
“…Improved microcirculation is known to promote nerve repair [11]; (2) VSD can promote the secretion of active substance of peripheral nerve, such as substance P, VEGF, platelet-derived growth factor (PDGF), transforming growth factor (TGF-β) [3,[12][13][14]. The role of the active substances including substance P, VEGF, PDGF.…”
Section: International Journal Of Neurosciencementioning
confidence: 99%
“…Furthermore, negative pressure protocols are typically used at one of two settings, namely, continuous or intermittent. In one previous study, intermittent suction was observed to cause a more profound tissue response compared with conventional methods; however, this suction mode may cause discomfort and intolerability in patients (32). In the present study, continuous negative pressure at a relatively high level of -200 to 300 mmHg was used on the wound beds.…”
Section: Discussionmentioning
confidence: 88%